Drilling speed-up and production-increasing development practice of ultra deep clastic reservoir based on Geology-Engineering integration in the Tarim Basin, Northwest China - Guodong Ji; Changchang Chen; Haige Wang; Hongchun Huang; Qiang Wu; Li Liu (Annals of Limnology and Oceanography - Peertechz Publications, 2022)
Kelasu structural belt in Tarim Basin has a large reservoir burial depth and complex geological conditions, and challenges such as ultra-deep, high temperature, high pressure, and high stress lead to big problems related to well control safety and project quality. To solve these key technical problems that set barriers to the process of exploration and development, a set of drilling technology processes via geology-engineering integration is established with geomechanics as the bridge. And an integrated key drilling engineering technology for the safe speed-up of ultra-deep wells was formed, integrating well location optimization, well trajectory optimization, stratum pressure prediction before drilling, stratum drillability evaluation, and bit and speed-up tool design and optimization. Combined with seismic data, logging data, structural characteristics, and lithology distribution characteristics, the rock mechanics data volume related to the three-dimensional drilling resistance characteristics of the block was established for the first time, and the vertical and horizontal heterogeneity was quantitatively characterized, which provided a basis for bit design, improvement, and optimization. During the process of drilling, the geomechanical model shall be corrected in time according to the actual drilling information, and the drilling "three pressures" data shall be updated in real-time to support the dynamic adjustment of drilling parameters. Through field practice, the average drilling complexity rate was reduced from 18% to 4.6%, and the drilling cycle at 8500 m depth was reduced from 326 days to 257 days, which were significantly better than those of the vertical wells deployed in the early stage without considering geology-engineering integration.